Willingness to pay for renewable energy among Indian small and medium-sized enterprises : a contingent valuation experiment - Wakuma, Samuel Tafesse (SLU/Dept. of Economics, 2018)
To limit climatic change, humans must achieve a reduction in greenhouse gas emissions. India, as a large emerging economy, could substantially contribute towards this goal by transforming its energy system. Based on a double-bounded dichotomous choice contingent valuation survey of 260 enterprises in and around Hyderabad, India, this paper provides willingness to pay (WTP) estimates of small and medium-sized firms for electricity generated from renewable sources. The estimated average additional willingness to pay was 1.08 Indian Rupees per kilowatt hour which constituted approximately 23% of the average tariff rate paid by the sector at the time of the study. The findings further suggest that WTP is driven by not only pure economic considerations but also managers’ attitudes – implying altruistic motives which might particularly be important in small firms. As a robustness check, the Heckman model was used to control for selection bias and protest responses. Additionally, the single-bounded probit model was employed to assess statistical efficiency gains from the second equation in the bivariate probit model. The estimated WTP suggests a market potential for additional private investments in renewable energy sources which, in combination with an effective tariff, could increase voluntary adoption rates of green energy tariffs.